Critical Ultrasound Journal - Volpicelli, Giovanni
Critical Ultrasound Journal is an international, peer-reviewed journal designed for clinicians using point-of-care ultrasound in any environment or setting. Critical Ultrasound Journal is the official publication of WINFOCUS (World Interactive Network Focused on Critical UltraSound), the world's leading scientific organization committed to developing point-of-care ultrasound practice, research, education, technology and networking and addressing the global needs of patients, institutions, services and communities living in out-of-hospital and in-hospital critical scenarios. The journal publishes editorials, reviews, original articles, short communications and case reports and is open for publication of supplements and abstracts of scientific meetings. By reaching audiences around the world, it plays a key role in bringing ultrasound to the patient's bedside, where this technique can make the greatest difference. The journal considers manuscripts within the fields of human health and it is open to contributions on the usefulness of ultrasound in animal care. Requirements and guidelines for submission of papers can be obtained from the publisher.